2007
DOI: 10.2298/aoo0702010p
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab in combination with oxaliplatin, irinotecan and fluoropyrimidine-based therapy in advanced colorectal cancer

Abstract: Background: Bevacizumab is an anti-VEGF, humanized mAb that is the most advanced agent of its class in clinical development. Several studies have examined bevacizumab in combination with chemotherapy in the first- and second-line settings in patients with metastatic CRC. Despite of that, there is lack of information concerning the extent to which bevacizumab can be used to treat metastatic CRC. We still need more evidence related to efficacy and safety of bevacizumab in different settings, or sequential treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Bevacizumab can be used not only in the first chemotherapy line. In some studies bevacizumab has been also used for patients who receive chemotherapy in the second or following chemotherapy lines 9,16 . The results of our study performed in Serbia suggest that bevacizumab should be used upfront rather than in second-line 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab can be used not only in the first chemotherapy line. In some studies bevacizumab has been also used for patients who receive chemotherapy in the second or following chemotherapy lines 9,16 . The results of our study performed in Serbia suggest that bevacizumab should be used upfront rather than in second-line 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only one study with bevacizumab has been performed in Serbia 9 . The aim of this study was to investigate efficacy and safety of bevacizumab added to different chemotherapy in patients with metastatic CRC.…”
Section: Bevacizumab In Combination With Oxaliplatin Irinotecan and mentioning
confidence: 99%
“…Bevacizumab is one of the newer monoclonal antibodies used as an additional treatment to current anticancer drugs in patients with mCRC. The results of so far clinical studies show that bevacizumab increased the therapeutic effect of 5-FU and oxaliplatin leading to the significant clinical improvement [9][10][11][12][13][14][15][16] . These findings were confirmed in our study, where the largest number of patients with complete and partial responses belong to the group of patients additionally treated with bevacizumab.…”
Section: The Influence Of Bevacizumab On Conventional Anticancer Agenmentioning
confidence: 99%
“…The results of several clinical studies have shown that the addition of bevacizumab to conventional anticancer drugs [5fluorouracil (5-FU), oxaliplatin, irinotecan, capecitabine)] greatly contributed to their therapeutic effect [9][10][11][12][13][14][15][16] . However, there were no data on its influence on the increased values of liver function tests parameters.…”
Section: Introductionmentioning
confidence: 99%